2016
DOI: 10.4236/abcr.2016.51001
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Intravenous vs. Subcutaneously Administered Trastuzumab for the Treatment of HER2+ Early Breast Cancer in Malaysia

Abstract: Human epidermal growth factor receptor-2 over expression has been reported in 23% -37.3% of Malaysian breast cancer patients. Trastuzumab is a recommended adjuvant therapy for patients with early breast cancer. Currently, trastuzumab is administered intravenously but a new subcutaneous formulation could save time and costs. In Malaysia, the Ministry of Health funds most of the costs of secondary care, including cancer treatment. We performed a cost-minimisation analysis from the Ministry of Health and societal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…First, the estimations of treatment and preparation time data by HCPs were obtained directly from the interviews, without being verified through direct observation, and could therefore be a source of recall bias. Nevertheless, since the estimated reduction in administration times observed in our study are consistent with those reported in similar studies in other countries [ 24 , 25 ], we can conclude this limitation is unlikely to have significantly influenced our study results. Our study included 10 hospitals from evenly distributed geographic sites across Spain, and although they were of different sizes, and included both public and private institutions, our results would likely have varied if hospitals different to these had been included in the study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, the estimations of treatment and preparation time data by HCPs were obtained directly from the interviews, without being verified through direct observation, and could therefore be a source of recall bias. Nevertheless, since the estimated reduction in administration times observed in our study are consistent with those reported in similar studies in other countries [ 24 , 25 ], we can conclude this limitation is unlikely to have significantly influenced our study results. Our study included 10 hospitals from evenly distributed geographic sites across Spain, and although they were of different sizes, and included both public and private institutions, our results would likely have varied if hospitals different to these had been included in the study.…”
Section: Discussionsupporting
confidence: 90%
“…Real-world studies have also consistently reported reductions in resource utilization and costs associated with conversion from IV to SC administration of rituximab and trastuzumab [ 12 , 14 , 15 , 17 , 24 , 25 ]. While these studies had similar conclusions, the magnitude of the estimated savings differed between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses were published between 2007 and 2017. For example, a costminimization analysis was conducted to determine the average cost of different routes of administration for trastuzumab in HER21 breast cancer, 39 and a budget impact analysis was done to determine the financial implication of peritoneal dialysis. 40 It was reported that 55% of the studies were conducted using the healthcare provider perspective, 29% adopted a societal perspective, and 13% reported mean costs based on both perspectives.…”
Section: Cost-consequence Cost-minimization and Budget Impact Analysesmentioning
confidence: 99%
“…The costs used in this analysis were based on MOH Consumer Price Guide from Pharmaceutical Services Program (2018), Malaysian DRG Casemix costing (severity illness 2), MOH Investigation Charges from website (2018), published literature using local data (Lee WC et al, 2016, Zainal R et al, 2014, Dranitsaris G et al, 2011, Hwa YS et al, 2011 and personal communication with pharmacists from National Cancer Institute, Malaysia. Direct medical costs included were cost of drugs, cost of procedures such as IV and subcutaneous administration of drugs, cost of investigations such as renal profile, cost of SRE related management (pathological fracture, radiotherapy to the bone and spinal cord compression requiring instrumentation), cost of specialist clinic follow-ups and palliative care.…”
Section: Resources and Cost Datamentioning
confidence: 99%